PROPUESTA DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO EN LA CÁMARA DE COMERCIO DE LOJA - Ramírez Godos, Gloria Esperanza (2019)
The present study proposes a feasibility proposal to determine the feasibility of creating a savings and credit fund, of closed origin, for the members of the Chamber of Commerce of Loja, in order to provide the union with a new financing alternative that drives the growth of their businesses and improves their income through the benefits obtained by saving. The development of the proposal was supported with the collection, analysis and classification of accurate and timely information collected with the survey that was applied through a simple random sampling to 252 partners of the Chamber of Commerce of Loja, which served to develop the Market Study, in which the socio-economic situation of the partners was analyzed, the average monthly income established in the category of $ 1501 to $ 3000 was known, the need for financing and also the approval of 594 partners was confirmed for the creation of the institution. The Technical Study was then carried out, where the optimal location of the savings account was established, the capacity that the institution will have to cover the demand for credit, and in the same way the minimum value of the contribution certificate was fixed, which is $ 37. Dollars. The Administrative-Legal Study was carried out, in which the Social Statute, Internal Regulation and Credit Manual were drawn up, which will govern the 5 operation of the cashier, together with the institutional philosophy and the levels of authority of the institution. Afterwards, the Economic-Financial Study was carried out, with which the investment amount of $ 15,878.35 was determined for the start-up of the project and the financing source to cover the costs and expenses of its implementation. On the other hand, the results obtained from the Financial Evaluation show a positive NPV of $ 77,860.45; the IRR of 67.73%; the Period of Recovery of Investment 2 years, 8 months and 26 days; a benefit of 0.59 cents, for each dollar invested and with an increase in costs of 17.50% will have a sensitivity of 0.98, with decrease in income of 12.30% the sensitivity will be 0.97. Given the reception by the partners for the creation of the savings bank, it is concluded that there is the necessary effective demand that duly supports the creation of the credit institution; In addition, it is economically beneficial in virtue of the results obtained. Therefore, the project is viable and profitable as an investment alternative for the members of the Chamber of Commerce of Loja.